The Deprivation of Women's Rights Due to Discrimination on the Marriage Age Limit - Herry Christian, Jordy; Edenela, Kirana (Lex Scientia Law Review, 2019)
In the 1945 Constitution of the Republic of Indonesia in article 27 paragraph (1) it is said that every citizen has the same position in law and government, but the Marriage Law No. 1 of 1974 which stipulates a difference in the minimum age limit for marriage, namely 16 (sixteen) years for women and 19 (nineteen) years for men, which creates discrimination against women and hinders the fulfillment of women's constitutional rights, namely the right to health, education and equality before the law. In its decision Number 22/PUU-XV/2017 asked the DPR to immediately revise the minimum age limit for marriage, but the Constitutional Court did not clearly stipulate the minimum age limit for marriage due to its open legal policy. Based on normative juridical studies, it can be concluded that the ideal minimum age for marriage is 18 years because it is in accordance with positive law in Indonesia and in accordance with global demands and eliminates discriminatory nature in the Marriage Law.